2018
DOI: 10.1186/s12891-018-1984-z
|View full text |Cite
|
Sign up to set email alerts
|

What factors impact on the implementation of clubfoot treatment services in low and middle-income countries?: a narrative synthesis of existing qualitative studies

Abstract: BackgroundAround 100,000 children are born annually with clubfoot worldwide and 80% live in low and middle-income counties (LMICs). Clubfoot is a condition in which children are born with one or both feet twisted inwards and if untreated it can limit participation in everyday life. Clubfoot can be corrected through staged manipulation of the limbs using the Ponseti method. Despite its efficacy and apparent availability, previous research has identified a number of challenges to service implementation. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
3
10
0
1
Order By: Relevance
“…The emerging role of community facilitators in reducing drop-out once the bracing phase starts, when most adherence falters [38][39][40][41][42], means additional staff and associated costs, but potentially may also in better rates of treatment completion, equating to less resource wastage and better results for more children in correcting clubfoot deformity, allowing them to lead happy and productive lives.…”
Section: Discussionmentioning
confidence: 99%
“…The emerging role of community facilitators in reducing drop-out once the bracing phase starts, when most adherence falters [38][39][40][41][42], means additional staff and associated costs, but potentially may also in better rates of treatment completion, equating to less resource wastage and better results for more children in correcting clubfoot deformity, allowing them to lead happy and productive lives.…”
Section: Discussionmentioning
confidence: 99%
“…De modo análogo as repercussões sobre a qualidade de vida citadas, essa revisão demonstrou que 86,7% dos artigos que compuseram o corpus documental apontaram para a eficácia elevada no tratamento do PTC de crianças mediante Técnica de Ponseti e a melhora significativa nos níveis de qualidade de vida (BHASKAR;PATNI, 2013;AYANA;KLUNGSØYR, 2014;MAHAPATRA;HAMPANNAVAR, 2014;MINDLER et al, 2014;ELGOHARY;ABULSAAD, 2015;HALLAJ-MOGHADDAM et al, 2015;SUGANDHAVESA et al, 2015;YILDIRIM et al, 2015;AGARWAL et al, 2016;CARPIAUX et al, 2016;EL BATTI et al, 2016;GRIMES et al, 2016;HECK;HECK;PLACZEK, 2016;JAQUETO et al, 2016;KHAN;KHANZADA, 2016;SEEGMILLER et al, 2016;LEBEL et al, 2017;MARQUEZ et al, 2017;MATAR et al, 2017;SHAH et al, 2017;SMYTHE et al, 2017;AGARWAL et al, 2018;DREW;GOOBERMAN-HILL;LAVY, 2018;JOCHYMEK;TUREK, 2018;MEHTANI et al, 2018). É importante destacar que a maior parte dos estudos apresentou nível de evidência I e II, os quais são os melhores e mais confiáveis.…”
Section: Discussionunclassified
“…Various studies worldwide have highlighted specific barriers to implementing the Ponseti method for clubfoot treatment. These barriers include poverty, cost of treatment, cost of traveling, caregiver's compliance to the treatment, and the parent responsible for the treatment, to list a few [10,[12][13][14][15][16][17]. The purpose of this study is to analyze the effect of these barriers on the dropout rates observed with the Ponseti method of clubfoot treatment.…”
Section: Introductionmentioning
confidence: 99%